2018
DOI: 10.1088/1361-6455/aac1ef
|View full text |Cite
|
Sign up to set email alerts
|

Calculations for electron impact ionization of Be atoms and its charged states, Be+and Be2+

Abstract: Electron impact triple differential cross section (TDCS) results are reported for the single ionization of Be(2s), Be(1s), Be 2+ (1s) and Be + (2s) targets. The differential cross sections have been calculated in the modified distorted wave formalism under different kinematical conditions for the coplanar emission of electrons. Due to unavailability of experimental data, we have made a careful comparison of Be and it's ions TDCS with the trends of TDCS measured for He and Li targets, which have similar electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
(81 reference statements)
1
2
0
Order By: Relevance
“…There are no experimental data available for the W atoms to compare with, but we compare the DWBA TDCS results obtained by us for the ionization of Xe (5p) at 1032 eV with the measurements [36] (Figure 6), which justifies the use of the DWBA approach for the present calculations. A good agreement was obtained with the measurements in case of Xe (5p) in present study (Figure 6), which was also the case for our earlier reported DWBA results for Xe (5p) [37], Ar (3s) [38], He (2s) [11], etc.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…There are no experimental data available for the W atoms to compare with, but we compare the DWBA TDCS results obtained by us for the ionization of Xe (5p) at 1032 eV with the measurements [36] (Figure 6), which justifies the use of the DWBA approach for the present calculations. A good agreement was obtained with the measurements in case of Xe (5p) in present study (Figure 6), which was also the case for our earlier reported DWBA results for Xe (5p) [37], Ar (3s) [38], He (2s) [11], etc.…”
Section: Resultssupporting
confidence: 93%
“…The TDCS obtained by this kind of study provides complete information about the collision dynamics involved. Following this, significant progress has been made in the study of the electron impact single ionization of various atomic, ionic and molecular targets and reasonable agreement has been obtained between the experimental and theoretical results [2][3][4][5][6][7][8][9][10][11][12][13]. As already mentioned, the electron-induced ionization of atomic as well as ionic targets is of prime importance for the diagnostics and modeling of fusion plasma.…”
Section: Introductionmentioning
confidence: 97%
“…The photon or charged particle (such as electron/positron/proton) induced ionization of targets like atoms, ions, molecules, and clusters is of prime importance in fundamental physics with important applications in the field of fusion plasma, atmospheric science, radiation physics related to live tissues, etc. Significant progress has been made in studying electron-induced single ionization processes, so-called (e, 2e) processes, for various atomic targets (see [1][2][3][4][5] and references cited therein) as well as molecular targets (see [6,7] and references cited therein). The ionization of atomic and ionic targets induced by charged particles is of particular importance for the modeling and diagnostics of fusion plasma.…”
Section: Introductionmentioning
confidence: 99%